Pelvic and Lower Gastrointestinal Tract Anatomical Characterization of the Average Male - Saffarzadeh, Mona; Eckert, Chad E; Nagle, Deborah; Weaner, Lauren S; Waters, Gregory S; Levine, Edward A; Weaver, Ashley A (Surgical innovation, 2019)
Colorectal surgeons report difficulty in positioning surgical devices in males, particularly those with a narrower pelvis. The objectives of this study were to (1) characterize the anatomy of the pelvis and surrounding soft tissue from magnetic resonance and computed tomography scans from 10 average males (175 cm, 78 kg) and (2) develop a model representing the mean configuration to assess variability. The anatomy was characterized from existing scans using segmentation and registration techniques. Size and shape variation in the pelvis and soft tissue morphology was characterized using the Generalized Procrustes Analysis to compute the mean configuration. There was considerable variability in volume of the psoas, connective tissue, and pelvis and in surface area of the mesorectum, pelvis, and connective tissue. Subject height was positively correlated with mesorectum surface area (P = .028, R = 0.47) and pelvis volume ( P = .041, R = 0.43). The anterior-posterior distance between the inferior pelvic floor muscle and pubic symphysis was positively correlated with subject height ( P = .043, r = 0.65). The angle between the superior mesorectum and sacral promontory was negatively correlated with subject height ( P = .042, r = -0.65). The pelvic inlet was positively correlated with subject weight ( P = .001, r = 0.89). There was considerable variability in organ volume and surface area among average males with some correlations to subject height and weight. A physical trainer model created from these data helped surgeons trial and assess device prototypes in a controllable environment.